ANALIZA CADRULUI LEGISLATIV PRIVIND PROBLEMELE COPIILOR RĂMAŞI FĂRĂ ÎNGRIJIRE PĂRINTEASCĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2011)
At a time when government responses to child and family policy issues are subject to radical change, this article analyses the principal areas of social policy affected by the needs of children and of parents. Over the past number of years there has been a significant refocus in the delivery of Child Welfare and Protection Services in Moldova. There has been a move towards developing family and community support initiatives in order to identify issues at an early stage and to address them within the context of the family, while at the same time ensuring high quality care structures for any child in need of them.